Algebra teacher's activities kit, grades 6-12 150 activities that support algebra in the common core math standards - Muschla, Judith A.; Muschla, Gary Robert; Muschla-Berry, Erin; Muschla,Gary Robert (Jossey-Bass Teacher, 2016)
"Help your students succeed with classroom-ready, standards-based activities The Algebra Teacher's Activities Kit: 150 Activities That Support Algebra in the Common Core Math Standards helps you bring the standards into your algebra classroom with a range of engaging activities that reinforce fundamental algebra skills. This newly updated second edition is formatted for easy implementation, with teaching notes and answers followed by reproducibles for activities covering the algebra standards for grades 6 through 12. Coverage includes whole numbers, variables, equations, inequalities, graphing, polynomials, factoring, logarithmic functions, statistics, and more, and gives you the material you need to reach students of various abilities and learning styles. Many of these activities are self-correcting, adding interest for students and saving you time. This book provides dozens of activities that Directly address each Common Core algebra standard Engage students and get them excited about math Are tailored to a diverse range of levels and abilities Reinforce fundamental skills and demonstrate everyday relevance Algebra lays the groundwork for every math class that comes after it, so it's crucial that students master the material and gain confidence in their abilities. The Algebra Teacher's Activities Kit helps you face the challenge, well-armed with effective activities that help students become successful in algebra class and beyond"--Provided by publisher.